Evidence from deuterium nuclear magnetic resonance for the temperature-dependent reversible self-association of erythrocyte band 3 in dimyristoylphosphatidylcholine bilayers. - Dempsey, C; Ryba, N; Watts, A (1986)
Band 3, isolated from human erythrocytes, has been reconstituted into bilayers of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) deuterated in the terminal methyl groups of the choline head group. By use of Triton X-100 for selective extraction and purification of band 3 and then cholate for subsequent solubilization with the lipid, a number of reconstituted complexes were produced by exhaustive detergent dialysis with protein:lipid weight ratios of between 0.32:1 and 1.25:1. Electron micrographs of negatively stained complexes showed that this method produced large vesicles of greater than 300-nm diameter. Deuterium nuclear magnetic resonance (NMR) spectra from the choline methyl deuterons in bilayer lipid above the liquid-crystal-gel phase transition temperature were shown to change systematically with increasing concentrations of band 3 in the bilayers. The measured quadrupole splittings, taken as the separation of the turning points in the recorded spectra, decreased from a value of 1.28 kHz for pure lipid to 0.98 kHz for bilayers with a protein:lipid ratio of 1.25:1 at 26 degrees C. At 35 degrees C, a more pronounced decrease in the quadrupole splittings was measured. The data from the complexes with protein:lipid ratios up to 0.7:1 (w/w) obey the mathematical treatment for a rapid two-site exchange between lipids at the protein-lipid interface and the bulk lipid phase. The temperature dependence of the measured quadrupole splitting with respect to the protein:lipid ratio indicates that the amount of lipid at the protein-lipid interface increases with increasing temperature.(ABSTRACT TRUNCATED AT 250 WORDS)